2015
DOI: 10.3109/10837450.2015.1041042
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin–Zn(II) complex for enhanced solubility and stability: an approach for improved delivery and pharmacodynamic effects

Abstract: This study recognizes higher solubility and stability of Curcumin-Zn(II) complex and suggested better pharmacodynamic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…The dose of curcumin used in this study was just 140 mg which was lower than the dose used in this study, indicating that curcumin indeed would be effective but with proper dosage and route of administration. There have been multiple studies on this aspect that have investigated various formulations of curcumin, some of which increase systemic bioavailability of curcumin and some have lead to increased colonic delivery[31,32]. In a mice study, Curcumin-Zn(II) complex was prepared by stirring curcumin with anhydrous zinc chloride at a molar ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of curcumin used in this study was just 140 mg which was lower than the dose used in this study, indicating that curcumin indeed would be effective but with proper dosage and route of administration. There have been multiple studies on this aspect that have investigated various formulations of curcumin, some of which increase systemic bioavailability of curcumin and some have lead to increased colonic delivery[31,32]. In a mice study, Curcumin-Zn(II) complex was prepared by stirring curcumin with anhydrous zinc chloride at a molar ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…In a mice study, Curcumin-Zn(II) complex was prepared by stirring curcumin with anhydrous zinc chloride at a molar ratio of 1:1. Kinetic stability studies showed a good stability of the metallo-complex with zinc and in vivo study revealed a significant reduction in severity and extent of colonic damage with this preparation[31]. Another study assessed the role of pH-triggered Eudragit-coated chitosan microspheres of curcumin in managing UC.…”
Section: Discussionmentioning
confidence: 99%
“…Priyadarsini (2014) [ 75 ] has comprehensively reviewed different extraction methods and curcumin conjugates, along with advances in improvements in curcumin delivery systems involving nanoparticles, due to hydrophobic nature of curcumin. Effective and simple chelation of zinc with curcumin to improve its bioavailability has been demonstrated [ 139 ]. Feed addition of curcumin to enhance immune status is well reported as reviewed earlier.…”
Section: Curcumin Extraction and Feed Applicationmentioning
confidence: 99%
“…Alongside the use of nanoparticles, liposomes, micelles, and phospholipid complexes to better improve the bioavailability of curcumin, curcumin complexation with transition metal ions represents yet another approach to circumvent the challenges mentioned above. In one study, it was found that a curcumin–Zn 2+ complex improved the solubility, stability, and the pharmacodynamic effects of curcumin . Because of the highly conjugated ß‐diketone moiety in the chemical structure of curcumin, it can readily form metal chelates of type 1:1 and 1:2 with various metal ions with divalent and trivalent inorganic molecules like Mn 2+ , Fe 2+ , Cu 2+ , Zn 2+ , Al 3+ , and Fe 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the highly conjugated ß‐diketone moiety in the chemical structure of curcumin, it can readily form metal chelates of type 1:1 and 1:2 with various metal ions with divalent and trivalent inorganic molecules like Mn 2+ , Fe 2+ , Cu 2+ , Zn 2+ , Al 3+ , and Fe 3+ . This results in the formation of metallocomplexes of curcumin, which may show greater effects as compared to free curcumin . Recent reports have demonstrated that the biochemical activities of curcumin are enhanced by metallocomplexes of curcumin .…”
Section: Introductionmentioning
confidence: 99%